SOSIALISASI BUDAYA DISIPLIN SEBAGAI PENGUATAN KARAKTER PESERTA DIDIK DI SMA NEGERI 6 GORONTALO - Sukarman Kamuli; Ariyanto Nggilu (Universitas Negeri Gorontalo, 2026)
This community service activity aims to increase students' understanding and awareness of the importance of a culture of discipline as part of character building at school. The activity was carried out at SMA Negeri 6 Gorontalo through socialization, counseling, discussion, and mentoring methods for students. Problems found at the school included the persistence of late arrivals to school, lack of compliance with rules, and low student awareness in maintaining learning discipline. Through the socialization of a culture of discipline, students were given an understanding of the importance of discipline in everyday life, both at school and in the community. The results of the activity showed an increase in students' understanding of the values of discipline, responsibility, and compliance with school rules.